Intrauterine programming of urinary calcium and magnesium excretion in children born to mothers with insulin dependent diabetes mellitus. Issue 4 (21st June 2005) - Mughal, M Z; Eelloo, J A; Roberts, S A; Sibartie, S; Maresh, M; Sibley, C P; Adams, J E
Abstract : Background: Offspring of diabetic rats have reduced urinary calcium and magnesium excretion compared with offspring of controls; these differences persist up to16 weeks after birth, a time equivalent to young adulthood in humans. Objectives: To test the hypothesis that urinary calcium and magnesium excretion would be lower in children born to mothers with insulin dependent diabetes mellitus (ChMIDDM) than those born to non-diabetic mothers. Methods: Concentrations of calcium, magnesium, sodium, and creatinine were measured in first void spot urine samples collected from 45 (28 male; median age 9.6 years) ChMIDDM and 127 (58 male; median age 11.3 years) controls. Analysis of covariance was used to test for differences in urinary calcium to creatinine ratios (UCa/Cr), magnesium to creatinine ratios (UMg/Cr), and log sodium to creatinine ratios (logUNa/Cr) between controls and ChMIDDM after allowing for the effects of sex and age. Results: UCa/Cr (difference −0.10, 95% confidence interval (CI) −0.19 to −0.01; p  =  0.03) and UMg/Cr (difference −0.15, 95% CI −0.22 to −0.08; p<0.0001) were lower in ChMIDDM than controls. However, logUNa/Cr did not differ between ChMIDDM and controls (difference −0.14, 95% CI −0.33 to 0.05; p  =  0.1). The daily estimated intake of magnesium, sodium, and protein were significantly higher and that of calcium non-significantly higher in ChMIDDM than controls. In ChMIDDM, UCa/Cr and UMg/Cr were not related to diabetic control of mothers. Conclusions: Results of this study provide the first evidence that in humans, as in rats, there is modification of renal Ca and Mg handling in ChMIDDM, which persists well into childhood.